The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.2147/copd.s418295
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Readmission, for Patients with Chronic Obstructive Pulmonary Disease (COPD) – A Systematic Review

Ronald Chow,
Olivia W So,
James HB Im
et al.

Abstract: Chronic obstructive pulmonary disease (COPD) is the third-leading cause of death globally and is responsible for over 3 million deaths annually. One of the factors contributing to the significant healthcare burden for these patients is readmission. The aim of this review is to describe significant predictors and prediction scores for all-cause and COPD-related readmission among patients with COPD. Methods: A search was conducted in Ovid MEDLINE, Ovid Embase, Cochrane Database of Systematic Reviews, and Cochran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 240 publications
1
2
0
Order By: Relevance
“…Our study also identified several sociodemographic and clinical variables that were associated with HR. In line with our findings, age and male sex have been consistently associated with a higher likelihood of HR (Chow et al., 2023; Lau et al., 2017). Both characteristics are indicative of a worse prognosis in respiratory patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study also identified several sociodemographic and clinical variables that were associated with HR. In line with our findings, age and male sex have been consistently associated with a higher likelihood of HR (Chow et al., 2023; Lau et al., 2017). Both characteristics are indicative of a worse prognosis in respiratory patients.…”
Section: Discussionsupporting
confidence: 92%
“…findings, age and male sex have been consistently associated with a higher likelihood of HR (Chow et al, 2023;Lau et al, 2017). Both characteristics are indicative of a worse prognosis in respiratory patients.…”
Section: Discussionmentioning
confidence: 83%
“…In COPD patients, male sex, previous hospitalization, poor performance status, long-term oxygen therapy, steroid use, mechanical ventilation, and decreased FEV 1 are risk factors for readmission. [18] Compared with the non-ARF group, the ARF group had a significantly higher risk of readmission within 1 year. However, in the 3-group analysis, only the type 1 ARF group had a significantly higher risk of readmission than the non-ARF group did.…”
Section: Discussionmentioning
confidence: 99%